2014
DOI: 10.3390/ijms150610083
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Insight into Tetracycline Resistant Bacteria and Antibiotic Resistance Genes in Activated Sludge Using Next-Generation Sequencing

Abstract: In order to comprehensively investigate tetracycline resistance in activated sludge of sewage treatment plants, 454 pyrosequencing and Illumina high-throughput sequencing were used to detect potential tetracycline resistant bacteria (TRB) and antibiotic resistance genes (ARGs) in sludge cultured with different concentrations of tetracycline. Pyrosequencing of 16S rRNA gene revealed that tetracycline treatment greatly affected the bacterial community structure of the sludge. Nine genera consisting of Sulfurital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Sulfuritalea , Armatimonas , Prosthecobacter , Hyphomicrobium , Azonexus , Longilinea , Paracoccus , Novosphingobium and Rhodobacter were identified as potential tetracycline resistant bacteria. Treatment of high-tetracycline wastewater increased both the abundance and diversity of the tet genes but decreased the occurrence and diversity of non-tetracycline ARGs (Huang et al 2014 ).…”
Section: Microbial Composition In Wwtpsmentioning
confidence: 99%
“…Sulfuritalea , Armatimonas , Prosthecobacter , Hyphomicrobium , Azonexus , Longilinea , Paracoccus , Novosphingobium and Rhodobacter were identified as potential tetracycline resistant bacteria. Treatment of high-tetracycline wastewater increased both the abundance and diversity of the tet genes but decreased the occurrence and diversity of non-tetracycline ARGs (Huang et al 2014 ).…”
Section: Microbial Composition In Wwtpsmentioning
confidence: 99%
“…If a certain level of drug is present in the environment, then ARB and ARG levels will not necessarily demonstrate the same pattern. For example, a number of different ARGs are known to confer resistance to a single drug, as seen with the multitude of ARGs for tetracycline (Huang et al, 2014), while single ARGs, like those for multidrug efflux pumps, can confer resistance to multiple drugs (Nikaido, 2009). Knowledge of the types of genes that confer resistance to particular antibiotics is necessary when analyzing an affected environment.…”
Section: Issues Linking Antibiotics and Antibiotic Resistance To Sourcesmentioning
confidence: 99%
“…Numerous studies have shown that ARB and ARGs related to quinolones (Lindberg et al, 2006;Kaplan et al, 2013), tetracyclines (Huang et al, 2014;Li et al, 2013), and sulfonamides (Collado et al, 2013;Gnida et al, 2014) could be found within various types of biosolids (nutrient rich organic matter that is a by-product of wastewater and sewage sludge treatment). Additionally, several antibiotic resistance plasmids including MDR pAS1 and RP4 carrying resistance to tetracycline, chloramphenicol, ampicillin, kanamycin, and many other antibiotics have been found in the diverse bacterial communities of activated sludge (Dröge et al, 2000;Parsley et al, 2010;Soda et al, 2008;Zhang et al, 2011).…”
Section: Biosolids (Land Application)mentioning
confidence: 99%
“…A factor with a significant effect on the ARG concentrations may also be the composition of the wastewater reaching WWTPs. Numerous studies have documented high concentrations of ARGs in wastewater produced by hospitals [6,23,30] or some industries, e.g., the food industry [11,20,38]. Moreover, dissemination of ARGs may also be affected by wastewater contamination with heavy metals, whose residues may pose co-selection pressure on ARG distribution [24].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in microbial diversity and the number of mobile genetic elements [18] and ARGs [19] is significantly affected by the activated sludge. Microorganisms forming particles of sludge are responsible for the accumulation and release of bacterial plasmids carrying ARGs [20], which facilitate the exchange of these genes between bacteria. Another factor contributing to the development of antibiotic resistance phenomenon during the wastewater treatment process is the presence of antibiotics, which, even at low concentrations, may induce genetic responses leading to adaptations and mutations among the microbial population [21].…”
Section: Introductionmentioning
confidence: 99%